The role of trade and sustainable intensification to achieve global food security with less carbon emission and more carbon sequestration - Piñeiro, Martín; Viglizzo, Ernesto; Laborde Debucquet, David; Loboguerrero, Ana Maria; Mirzabaev, Alisher; Frank, C. Federico; Buainain, Antonio (T20 Argentina, 2018)
According to some estimates food production needs to increase 60% by 2050 to meet the expected demand and assure food security for all. In order to meet this target and simultaneously achieve the carbon emission targets set in the Paris agreement it is necessary to restructure agricultural production in a substantial way.